2019
DOI: 10.21573/vol35n32019.95957
|View full text |Cite
|
Sign up to set email alerts
|

Militarização das escolas e a narrativa da qualidade da educação

Abstract: Por meio de uma pesquisa documental e bibliográfica o trabalho tem por objetivo analisar as concepções e condições para a qualidade manifesta na defesa dos colégios militares e escolas cívico-militares. Enquanto resultados mostraremos que por trás do resgate da pedagogia militar da educação, os padrões de qualidade reproduzem a mesma dinâmica dos sistemas de avaliação dos governos anteriores, silenciando ainda as condições materiais que legitimam os supostos desempenhos acadêmicos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…It is suggested that, for the samples evaluated, the Creative Personal Identity and Creative Self-Efficacy of the students are independent of the type of school and sex. This result confronts the sometimes-stereotyped assumption that characteristics of the military learning environment limit or impede the students' development (Calbino et al, 2019;Lacé et al, 2019;Roseiro et al, 2020;Soares et al, 2019), particularly the development of creativity.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is suggested that, for the samples evaluated, the Creative Personal Identity and Creative Self-Efficacy of the students are independent of the type of school and sex. This result confronts the sometimes-stereotyped assumption that characteristics of the military learning environment limit or impede the students' development (Calbino et al, 2019;Lacé et al, 2019;Roseiro et al, 2020;Soares et al, 2019), particularly the development of creativity.…”
Section: Discussionmentioning
confidence: 86%
“…Scholars highlight non-cognitive qualities of students stressed in militarized pedagogical models, such as discipline, hierarchy, cooperation, hygiene, and group values (Hajjar, 2005;Price, 2008;Vego, 2013). On the other hand, this model is subject to criticism, highlighting damages to the student's critical sense, arising from a culture of fear (Calbino et al, 2019;Lacé et al, 2019;Soares et al, 2019). Pezzi et al (2016) argues that, throughout history, Brazilian public school has presented successive demonstrations of school failure, especially with regard to proficiency and failures.…”
Section: Creative Self-beliefs Of Civilian and Military School Studentsmentioning
confidence: 99%
“…Temas como religión (centrado en el evangelismo fundamentalista), familia (a partir de una lectura muy conservadora) y el ultraliberalismo económico son defendidos por las principales autoridades del país, siendo que, después de tres años del inicio del gobierno Bolsonaro, ya se logró ocupar distintos cargos importantes para que exista una red de imposición de esta agenda, conformando lo que algunos autores y autoras llaman de "erosión democrática" provocada por movimientos de extrema derecha (Solano, 2019;307-321). La agenda de privatización de diversos sectores de la educación a partir de la disminución gradual del presupuesto público de las universidades públicas, hasta el punto en que no haya recursos suficientes como para mantener sus actividades (Chaves, 2020); la militarización de escuelas primarias y secundarias públicas como forma de "aumentar la calidad de la educación" (Pinheiro, 2019;667); el favorecimiento de empresarios de grandes conglomerados educacionales (Souza, 2020; 421-229) y de líderes religiosos para la destinación de recursos públicos del Ministerio de Educación (O Globo, 2022) y la facilitación de aperturas de cursos superiores a distancia (Malanchen, 2020) -algo que la pandemia abrió un espacio aún más amplio-provocó un proceso de fuerte depreciación de la educación brasileña como estructura. Sin embargo, todos estos eventos fueron resultado de la decisión del Poder Ejecutivo Federal (y, en algunos casos, de algunos estaduales que apoyan al gobierno federal), lo que, hasta el momento, no dio la oportunidad de control por parte del STF.…”
Section: Los Ataques Al Derecho a La Educación En Brasil En El Gobier...unclassified
“…The Bolsonaro government assumed for itself the defense of a series of moral values that have historically adhered to the table of values of Brazilian Protestants since the nineteenth century, especially the defense of the family, the fight against the profanity of folklore and national festivals, demonization of African and indigenous culture, and the fight against illicit drugs (Pesquisa Fapesp 2019 ). At the same time, Bolsonarism promoted new values among evangelical Christians, which were endorsed without great resistance, such as the policy of proliferation of weapons among “good citizens” (Paschoal 2020 ); the project of moralizing politics and education through its militarization (Pinheiro et al 2019 ); and critical action against other powers of the Republic, at the same time that the Military Dictatorship of 1964–1985 is praised and Bolsonaro’s political opponents are classified in the “communist” category (Camargo et al 2020 ).…”
Section: Bolsonarism and The Brazilian Evangelical Movement: Synergiementioning
confidence: 99%